2016
DOI: 10.1038/nsmb.3257
|View full text |Cite
|
Sign up to set email alerts
|

Free backbone carbonyls mediate rhodopsin activation

Abstract: Conserved prolines in the transmembrane helices of G protein-coupled receptors (GPCRs) are often considered to function as hinges that divide the helix into two segments capable of independent motion. Depending on their potential to hydrogen-bond, the free C=O groups associated with these prolines can facilitate conformational flexibility, conformational switching or stabilize receptor structure. To address the role of conserved prolines in family A GPCRs, we focus on bovine rhodopsin, a GPCR in the visual rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…In rhodopsin, a central role of D83 appears to be stabilization of the dark state via H-bonds to N55 and a water molecule that is bonded to other residues [7,33,34]. Site N55 forms a H-bond with the carbonyl backbone of A299 in the dark state, which creates an indirect H-bond link between site 83 and site 299 (D83-N55-A299) [33,35]. During light activation, breakage and reformation of H-bonds in this network are key mechanisms by which the transmembrane helices rotate into the meta II conformation [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rhodopsin, a central role of D83 appears to be stabilization of the dark state via H-bonds to N55 and a water molecule that is bonded to other residues [7,33,34]. Site N55 forms a H-bond with the carbonyl backbone of A299 in the dark state, which creates an indirect H-bond link between site 83 and site 299 (D83-N55-A299) [33,35]. During light activation, breakage and reformation of H-bonds in this network are key mechanisms by which the transmembrane helices rotate into the meta II conformation [34].…”
Section: Discussionmentioning
confidence: 99%
“…During light activation, breakage and reformation of H-bonds in this network are key mechanisms by which the transmembrane helices rotate into the meta II conformation [34]. In particular, recent work using solid-state NMR spectroscopic techniques have confirmed that the N55-A299 bond is broken during the transition to meta II [35]. This breakage may be due in part to reorientation of the N55 amine group away from A299 and towards D83 as seen in the bovine meta II crystal structure (figure 4a), which strengthens the D83-N55 bond [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…At the other end of this network, the free C¼O at Ser7.46 hydrogen bonds with Asn1.50. A loss of the hydrogen bonding between Ser7.46 and Asn1.50 (51), and a corresponding increase in hydrogen bonding of the Asp2.50 carboxylic acid side chain (53) are observed upon rhodopsin activation. These changes may alter the local distortions of H7.…”
Section: Location Of the Packing Clusters Relative To The Activation mentioning
confidence: 99%
“…Although Pro5.50 forms important packing interactions, it also gives rise to a free C¼O group at position 5.46 that is able to switch hydrogen-bonding interactions upon activation. The free C¼O group associated with Pro7.50 also appears to function as a hydrogen-bonding switch in the second activation switch (see below) (51).…”
Section: Location Of the Packing Clusters Relative To The Activation mentioning
confidence: 99%
“…41 Many structural studies reveal complex helix movements involving the rearrangements of H-bonding in the transmembrane region of the protein, and several states of the chromophore relaxation during activation. [21][22][23][24][25][26][27]42 Since the structural studies that reveal those motions are carried out by trapping intermediates at low temperatures and only some of the intermediates are likely to be trapped at low temperature, it is not possible to identify specific structures with specific intermediates observed here. Such correlations will require time-resolved structural studies under conditions that are comparable to photolysis conditions used in this study.…”
Section: ■ Conclusionmentioning
confidence: 99%